Quando a infância pede refúgio: os processos de crianças no Comitê Nacional para os Refugiados - Lazarin, Monique Roecker (2019)
The present research emerges with the global scenario of intensification of displacement of refugees, nevertheless with the attentive look at the great participation of children. In Brazil, there is also an increase in requests for refuge, but there is no data to explain which part of this population includes children. Thus, this research has the objective of mapping out which range off childhood has become a refugee in Brazil, based on the quantitative analysis of the children who make it up. This refugee childhood is understood here as one of the many facets that involve the social phenomenon of childhood contemporaneously. The analysis of the composition is guided by the understanding that such childhood is not only formed by those children who have received recognition of the refugee status by Brazil; it is, on the other hand, constructed from the universe of requests of children that has been made to the country and that are segmented in diverse statuses. This organization is in agreement with the theoretical foundation that conceives refuge as a social process emerged in the governmentality of people: either expelling some of them from their country, as is the moment of emigration, or administering the immigration flows that enter the territories. In other words, the displacements of children are intermediated by migration policies. The methodology used for this purpose is statistical analysis of secondary data, using the table provided by the Comitê Nacional para Refugiados (Conare), which lists the cases registered until April 2016. The research has social and sociological relevance, because it contributes to the understanding of migration flows directed to Brazil, bringing data of great importance to public migratory policies, at the same time that feeds a debate yet little observed by Sociology. About this last aspect, the bibliographical review of the Brazilian articles that deal with the subject portrays that this is not a subject of many debates in the Brazilian researches and, lesser, in Sociology. Thus, by its double aspect, this research brings contributions both to migratory studies as all as to social studies on Childhood. As results, we highlight that the refugee childhood is constituted by the multiplicity: of applicants and of framing for such requests. It is also perceived that the infantile flows of refugees to Brazil do not follow the same pattern of adult flows and should not, therefore, be simply analyzed as a derivation. It is also identified that the refugee immigration of children in the country does not follow the same intensity that occurs at international level, in proportional terms of composition of the age groups of such flow. Another point that the data analysis demonstrates is that the management of these requests, through process judgments, promotes a significant change in the situation of refugee children, by not keeping similar proportions of the universe of child demands within status.